Seleção, comportamento fenotípico e genotípico e desenvolvimento de uma nova cultivar de abóbora (Cucurbita moschata Dusch) - Silva, Thássia Barbosa da (2010)
The aim of this work was to evaluate the phenotypic and genotypic behavior and to develop a new cultivar of pumpkin (Cucurbita moschata Dusch), with cordiform fruits and fruits with thick pulp. To obtain the S0 generation (original population), fruits were collected in production areas and they presented the following characteristics: cordiform fruits, thick pulp, orange colored pulp, fruit weight between 5 and 7 kg. Seeds were planted and the plants were selfed to produce the S1 generation. The same method was used to produce the S2 generation, followed by recombination. Means, standard error and amplitude of the generations were estimated and reduction of the values. The following parameters also were estimated: heritability, genetic variance, variance of the interaction genotype x environment, coefficient of genetic variation (CVg), coefficient of environmental variation (CVe) and the relation CVg/CVe. The high heritability values associated with the genetic variance values major the genotype x environment variance shows a not significative influence of the environment for the studied characters, which facilitate the development of new pumpkin cultivar. At the second part of this work competition assays were realized in two agriculture years, 2008 and 2009, and for the variables pulp thick, fruit width, and number of seeds the ABO-MELHOR population obtained means of 4 cm, 19.69 cm and 568.66, respectively. The genetic breeding program resulted in the development of the new pumpkin cultivar 'Tiêta'.